2017
DOI: 10.1021/jacs.6b08313
|View full text |Cite
|
Sign up to set email alerts
|

Smart Nanostructures for Cargo Delivery: Uncaging and Activating by Light

Abstract: Nanotechnology has begun to play a remarkable role in various fields of science and technology. In biomedical applications, nanoparticles have opened new horizons, especially for biosensing, targeted delivery of therapeutics, and so forth. Among drug delivery systems (DDSs), smart nanocarriers that respond to specific stimuli in their environment represent a growing field. Nanoplatforms that can be activated by an external application of light can be used for a wide variety of photoactivated therapies, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
251
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(256 citation statements)
references
References 297 publications
(809 reference statements)
1
251
0
1
Order By: Relevance
“…A lot of drug delivery systems have been developed to realize combination chemotherapy and photothermal ablation. For instance, chemical drugs were directly loaded in photothermal nanoparticles, such as gold,19, 20, 21, 22 sulfide,23, 24, 25, 26 graphene and graphene‐like materials,27, 28, 29, 30 Prussian blue;31, 32 or loaded in mesoporous silica, smart polymer, aptamer, and cleavable linkages etc. modified on the photothermal particles 33, 34.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of drug delivery systems have been developed to realize combination chemotherapy and photothermal ablation. For instance, chemical drugs were directly loaded in photothermal nanoparticles, such as gold,19, 20, 21, 22 sulfide,23, 24, 25, 26 graphene and graphene‐like materials,27, 28, 29, 30 Prussian blue;31, 32 or loaded in mesoporous silica, smart polymer, aptamer, and cleavable linkages etc. modified on the photothermal particles 33, 34.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the shallow light penetration depth, drug release using these incident light causes severe side effects, particularly the phototoxicity. Therefore, the development of more reliable alternatives that enable a high depth tissue penetration and more precise control of photoactivation reaction as well as minimum cellular damage is of clinical importance …”
Section: Nir Light Controlled Drug Delivery Systemsmentioning
confidence: 99%
“…In addition, it has been suggested that the hydrolytic attacks by proteases in the skin and blood/lymphatic network may also limit the bioavailability of MN-administered proteins [60]. Therefore, appropriate materials and formulations to preserve the protein integrity and improve the delivery efficiency are highly desirable for this form of therapy [61,62]. In this section, typical protein therapeutics and their properties associated with MN-mediated delivery approaches are briefly surveyed.…”
Section: Types Of Delivered Proteinmentioning
confidence: 99%